Ijtihad Khalifah Uṡmān bin ‘Affān dan Implikasinya dalam Perekonomian Islam - Ahmad Syaripudin; Sulkifli Herman; Ahmad Marwazi Manar (AL-KHIYAR: Jurnal Bidang Muamalah dan Ekonomi Islam, 2021)
This research aims to examine the biography of the life of the friend of Uṡmān bin 'Affān ra., the methods and results of ijtihad of the companions and caliphs in the time of the caliphate Uṡmān bin 'Affān ra. in the Islamic economy. Research methods use qualitatively oriented library research in data collection with historical and normative approaches. The results showed that: first, from the biography of Uṡmān bin 'Affān it was found that he had the character of the leader of the rabbani in terms of knowledge, directing ability, and providing education, generosity, tolerance, gentleness, forgiveness, laughter, high shame, guarding himself, generous, brave, firm, firm, patient, fair, worship, wara’, easy to cry, fond of self-evaluation, zuhud, good at gratitude, looking for solutions to people's lives, looking for uniqueness and benefiting from its community specialists. Second, ijtihad Uṡmān bin 'Affān ra. In the islamic organization is upright on the general basis of its direction on the method of zakat, not neglecting tax attention to the people, taking what is the obligation of muslims to Baitulmal, taking what is the obligation of experts to Baitulmal properly, educating tax officials with a trustworthy nature, and keeping promises and eliminating financial irregularities that are stimulated in society. Third, the results of ijtihad had an impact on the financial distribution during the time of Uṡmān bin 'Affān ra. It was used to pay the salaries of governors and soldiers, build a maritime fleet, build and expand the al-Haram mosque and the Prophet's mosque, create springs to drink, subsidize materil to the muezzin.